Construction and use of Social Accounting Matrices - Santos, Susana (2022)
In adherence to the central framework of the current version (2008) of the System of National Accounts (SNA), our construction will be based on an illustration for Portugal of a complete sequence of national accounts in its various forms - published in: https://mpra.ub.uni-muenchen.de/114636/; also available, with an excel file, in: http://hdl.handle.net/10400.5/25561. By adopting a top-down method, that is to say, starting from an aggregate level and then showing the path to possible disaggregations and extensions, the matrix forms, or matrix representations, presented after the T-accounts/tables are organised into two parts: 1) supply and use tables and inputoutput matrices; 2) accounting matrices. Emphasis will be placed on “accounting matrices”, in which the two kinds of information recorded by the national accounts – flows and stocks – will have specific treatments. Among flows, transactions, to which special attention is usually paid, will initially be worked on separately, and then together with other flows and stocks, albeit in a different way. Thus, our construction will start at the level of transactions, i.e., at the level of the current accounts and a particular part of the accumulation national accounts – capital and financial. This part will not consider the consumption of fixed capital and will be worked on in gross terms. The other part of our construction will be at the level of other flows and stocks, as well as certain transactions. All the accumulation accounts – capital, financial, other changes in the volume of assets, and revaluation – and also the balance sheets will be represented. This part will consider the consumption of fixed capital and will be worked on in net terms. We will present a matrix representation that we will call “National Accounting Matrix (NAM)” – which SNA calls a “Social Accounting Matrix”, from another that we will call “Social Accounting Matrix (SAM)”, in a version conceived from the study of the works of R. Stone, G. Pyatt, and J. Round, among others. The two above-mentioned parts of our construction can be understood as being a basis for the study of income and wealth, respectively. The matrix form will also facilitate working with networks of linkages, namely, inter-institutional, and intra-institutional. Accordingly, guidelines will be provided to study in more depth, on the one hand, the generation, distribution, redistribution, and accumulation of income, and, on the other hand, the accumulation and distribution of wealth. The purposes of the studies will define the desired uses of constructed matrices. To this end, as defined by the SNA, possible disaggregations will be addressed within the scope of its central framework, leaving the extensions, associated with special purposes, to the satellite accounts.